Puding Jagung dan Daun Kelor Untuk Perbaikan Status Gizi Sebagai Langkah Antisipasi Penyebab Stunting Sejak Usia Subur Pada Remaja Putri - Hajidzah, Santi Nur; Karo, Marni Br; Manullang, Riyen Sari (Universitas Respati Indonesia, 2025)
Background: Nutritional well-being is the result of the consumption, absorption, and utilization of nutrients in the body, which can be observed through BMI, MUAC, and hemoglobin levels in adolescents. Reproductive health, which plays a crucial role in producing the next generation, is greatly influenced by nutritional status. Indonesia still faces serious nutritional problems, one of which is stunting due to long-term nutritional deficiencies, especially in the first 1,000 days of life. This condition is exacerbated by unbalanced nutritional intake from adolescence, as a childbearing age group. This can be addressed by consuming nutritious foods, one of which is corn pudding and moringa leaves, which contain nutrients good for the body, especially in adolescence. Purpose of the study: To determine the effectiveness of providing corn pudding and moringa leaves in improving nutritional status as a preventative measure for the causes of stunting from a childbearing age in adolescent girls at Widya Nusantara High School. Method: The study design used a quasi-experimental approach with a One Group Pre and Post Test Design. Adolescent girls were given corn pudding and moringa leaves three times a week for one month. Results: The statistical test results showed a significance value of 0.000 (p < 0.05), so H0 was rejected. This proves that regular consumption of Corn Pudding and Moringa Leaves is effective in improving the nutritional status of adolescent girls at Widya Nusantara High School. Conclusion: There was a significant increase in nutritional status before and after the intervention, so Corn Pudding and Moringa Leaves can be used as an alternative in efforts to anticipate stunting in adolescent girls.